2010
DOI: 10.1007/s10903-010-9347-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence Among Canadian Immigrants, 1980–1998: Results from a National Cohort Study

Abstract: Canadian immigrants have lower overall cancer risk than the Canadian-born population. Less is known about risks for immigrant subgroups and site-specific cancers. Linked administrative data sets were used to compare cancer incidence between subgroups of immigrants to Canada and the general Canadian population. The study involved 128,962 refugees and 241,010 non-refugees. Standardized incidence ratios (SIRs) were calculated for all-site and site-specific cancers by immigration categories and regions of birth. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 31 publications
5
36
0
3
Order By: Relevance
“…These findings extend the work of others 10 by providing subnational analyses and are consistent with individual-level based analyses which also found lower rates of most cancers among immigrant groups. [10][11][12] Exceptions to the reported pattern were found for liver, thyroid and nasopharynx cancers where more elevated incidence occurred within these same high concentration foreign-born areas. These national findings are similar to what had been reported for liver cancer using area-based information for Ontario.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings extend the work of others 10 by providing subnational analyses and are consistent with individual-level based analyses which also found lower rates of most cancers among immigrant groups. [10][11][12] Exceptions to the reported pattern were found for liver, thyroid and nasopharynx cancers where more elevated incidence occurred within these same high concentration foreign-born areas. These national findings are similar to what had been reported for liver cancer using area-based information for Ontario.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have used record linkage to conduct cancer surveillance. 10,11 However, data are not routinely available to conduct national and comparable regional cancer surveillance by a person's foreign-born status in order to track incidence in this subpopulation. The objective of this study is to apply a standardized area-based measure to examine whether or not estimated cancer incidence rates among individuals living in given areas vary systematically according to the concentration of foreign-born individuals living in the same given areas.…”
mentioning
confidence: 99%
“…27 Although available data suggest that some women would prefer to undergo screening despite its potential harms, many would not. [28][29][30][31][32][33] These data show that determining the preferences of individual women about the relative importance of potential benefits and harms is critical in determining who should undergo screening. Sources of information for women should accurately portray the value of mammography and the potential for harm rather than simply provide encouragement.…”
Section: Considerations For Implementationmentioning
confidence: 99%
“…Certain ethnic groups may have higher (e.g., Ashkenazi Jews) 36 or lower (East Asians) 33 risk of death from breast cancer, which may alter the absolute benefit of screening. Rates of screening are low among Aboriginal populations, 3 7 , 3 8 women with low incomes and recent immigrants; 39 further work is needed to explain these findings and determine their potential impact.…”
Section: Considerations For Implementationmentioning
confidence: 99%
“…[5][6][7][8][9] There are limited and controversial epidemiological data concerning whether immigration may cause significant changes in the risk and mortality of gynecological cancers. [10][11][12][13][14][15][16][17] For example, a persistent high cervical cancer risk was reported among North African immigrants in Israel, 15 whereas, in contrast, a study on Korean immigrants in the United States showed a decreased risk of cervical and an increased risk of endometrial cancers. 17 It has been reported that East African immigrants in England and Wales experienced decreased cervical and ovarian cancer mortality rates compared to English and Welsh natives.…”
mentioning
confidence: 99%